A vinylogous Michael addition-triggered quadruple cascade reaction for the enantioselective generation of multiple quaternary stereocenters. Issue 10 (14th January 2019) - Yang, Shu-Mei; Karanam, Praneeth; Wang, Min; Jang, Yeong-Jiunn; Yeh, Yu-Sheng; Tseng, Ping-Yao; Ganapuram, Madhusudhan Reddy; Liou, Yan-Cheng; Lin, Wenwei
Abstract : An efficient organocatalytic vinylogous Michael addition-triggered quadruple cascade reaction resulting in fused spiroxindoles bearing multiple quaternary stereocenters is demonstrated from β-trifluoroacetylarylidene indanediones and 3-alkylideneoxindoles. Abstract : An efficient organocatalytic quadruple cascade reaction resulting in spiroxindole scaffolds bearing five quaternary stereocenters is reported. The complex cascade reaction is triggered by the scarcely explored vinylogous Michael addition of 3-alkylidene oxindoles to fully substituted enones and demonstrates the usefulness of the latter as efficient Michael acceptors in generating complex caged products in 26–92% yields, 14–98% ee and up to >25 : 1 d.r. values.